High time resolution measurements of the thermosphere from Fabry-Perot Interferometer measurements of atomic oxygen - Ford, EAK; Aruliah, AL; Griffin, EM; McWhirter, I (EUROPEAN GEOSCIENCES UNION, 2007)
Recent advances in the performance of CCD detectors have enabled a high time resolution study of the high latitude upper thermosphere with Fabry-Perot Interferometers (FPIs) to be performed. 10-s integration times were used during a campaign in April 2004 on an FPI located in northern Sweden in the auroral oval. The FPI is used to study the thermosphere by measuring the oxygen red line emission at 630.0 nm, which emits at an altitude of approximately 240 km. Previous time resolutions have been 4 min at best, due to the cycle of look directions normally observed. By using 10s rather than 40s integration times, and by limiting the number of full cycles in a night, high resolution measurements down to 15 s were achievable. This has allowed the maximum variability of the thermospheric winds and temperatures, and 630.0 nm emission intensities, at approximately 240 km. to be determined as a few minutes. This is a significantly greater variability than the often assumed value of 1 h or more. A Lomb-Scargle analysis of this data has shown evidence of gravity wave activity with waves with short periods. Gravity waves are an important feature of mesosphere-lower thermosphere (MLT) dynamics, observed using many techniques and providing an important mechanism for energy transfer between atmospheric regions. At high latitudes gravity waves may be generated in-situ by localised auroral activity. Short period waves were detected in all four clear nights when this experiment was performed, in 630.0 nm intensities and thermospheric winds and temperatures. Waves with many periodicities were observed, from periods of several hours, down to 14 min. These waves were seen in all parameters over several nights, implying that this variability is a typical property of the thermosphere.